CONFLICT POTENTIAL OF THE CONCEPT WILLKOMMENSKULTUR IN GERMAN LANGUAGE INTERCULTURAL DISCOURSE - Mikhidenko, Kateryna (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
This article is dedicated to the research of the concept of German language intercultural discourse WILLKOMMENSKULTUR and to the analysis of its ways of verbalization in the communicative process. The analysis of the concept verbalization is based on the comments and posts of users of German language forums and chat-rooms, which allows to research unprepared spontaneous expressions, as close to real speech as possible. Being mental structure units of the human mind concepts do not only help to structure new knowledge, but they also to a significant extent construct the reality perceived by an individual as a representative of a specific sociocultural space. In the light of actual social-political events, the concept WILLKOMMENSKULTUR becomes currently of great importance containing ideas of the relationship between the German speaking society and the foreigners or citizens with migration background. Thereby the role of the German language society as the receiving party involves intercultural competence, tolerance towards other cultures and traditions different from one's own as well as the willingness to welcome representatives of a different ethno-cultural environment, thus creating a society with high development potential. But along with such an idealized interpretation of welcome culture, with the background of actual social-political development the idea of "Willkommenskultur" attains a new, deeply negative form and, as a result, a new, completely opposite concept emerges. In the negative sense the concept WILLKOMMENSKULTUR depicts the fear of the society that the "the guests" of their country slowly turn to "hosts" while the native population is forced to reject own traditions and culture due to a new one, imposed on them by the foreigners. Such an understanding of "Willkommenskultur" implies the inability of the native population to protect its own principles and, as a result, gradual self-destruction. The paper analyses the conceptual fields of both forms of interpretation of the concept WILLKOMMENSKULTUR and its reinterpretation according to the actual events in German language society, which allows to analyze the cogitation patterns of the speakers as well as society's conflict questions and urgent problems that find their way into the intercultural conflict discourse.____________ReferencesKamenskaja O. L. Tekst i kommunikacija [Text and communication]. Vysshaja shkola, 1990. – 152 p. (In Russian)Makarov M.L. Osnovy teorii diskursa [Main theories of discourse].: Gnozis, 2003. – 276p. (In Russian)Bundesamt für Migration und Flüchtlinge: Willkommens- und Anerkennungskultur (BAMF, 2013), доступ http://www.bamf.de/SharedDocs/Meldungen/DE/2011/20110519-nuernberger-tage-integration-willkommenskultur.htmlMerx A., Ruster J., Szukitsch Y. Willkommenskultur (und Anerkennungskultur): Hintergrund, Diskussion und Handlungsempfehlungen (München, IQ - Fachstelle Diversity Management, 2013),Nonhoff M. Diskurs. Radikale Demokratie. Hegemonie. Zum Politischen Denken von Ernesto Laclau und Chantal Mouffe (Verlag Bielefeld, 2007),https://www.tagesspiegel.de/politik/repraesentative-umfrage-mehrheit-der-deutschen-beklagt-fehlende-toleranz/23099372.htmlhttps://mobile.twitter.com/y03y_2fknSt0n3D/status/1040340933324222465?p=vhttps://bundesdeutsche-zeitung.de/headlines/politics-headlines/unterwerfung-deutschland-ist-zu-tolerant-gegenueber-dem-islam-970720
Keywords: concept, cognitive field, intercultural discourse, conflict discourse, welcome culture